De l’imaginaire des retombées au Bunker Bildungsroman : l’imaginaire nucléaire après l’utopie - Anindita Banerjee (ReS Futurae)
Using two concepts providing by the Tarkovskij and Aleksievič’s works (Stalker and Voices from Chernobyl), scaling down the nuclear in terms of both space and time and the idea of contaminated fiction, the article focuses on the Metro 2033 phenomenon. Through the structures and capabilities of transmedia storytelling, Metro 2033 transforms fallout fantasy into a new, collaboratively produced and performed narrative, coined “bunker bildungsroman”, fostering hyper-reading and participants’ own narratives of emergence. The multidirectional, dialogic interpretation between the real, the imaginary, the lived and the speculative potentialities of the nuclear mobilizes the bunker bildungsroman into a powerful handbook of living.